Economic valuation for tembawang ecosystem, in Sanggau District, West Kalimantan, Indonesia - EMI ROSLINDA; SITI MASITOH KARTIKAWATI; RABUDIN RABUDIN (Society for Indonesian Biodiversity, 2017)
Roslinda E, Kartikawati SM, Rabudin. 2017. Economic valuation for tembawang ecosystem, in Sanggau District, West Kalimantan, Indonesia. Biodiversitas 18: 1506-1516. The tembawang ecosystem in West Kalimantan (Indonesia) spreads over especially in Sanggau District region. Tembawang is a system of land used by customary community of Dayak ethnic which is traditionally managed and communally used. The objective of this study is to determine the total economic value (TEV) of the tembawang ecosystem. Survey methods were used in this research. 70 respondents were selected by census method. Total economic values in this research were restricted on direct use value, indirect use value and option value. Based on market price (biomass) and opportunity cost (hydrological role), the economic values were calculated. The results showed that total economic value of Tembawang Ampar was IDR 263,837,082 year-1, which was equivalent to IDR 36,900,291 year-1ha-1. They are IDR 33,545,791 year-1ha-1 from direct use value, IDR 3,072,738 year-1ha-1 from indirect use value, and IDR 281,762 year-1ha-1 from option value. Total economic value of tembawang was rather low. The low of economic value was due to limited benefits assessed in this study. Whereas in fact, there were many benefits from tembawang obtained by the community. Conserving tembawang ecosystem will not be achieved by simply considering the conservation of species in tembawang, but the preservation will need to encompass a wide range of natural resources and the potential services provided by them.